IMPLEMENTASI RUMUS SOBEL PADA WEB DENGAN TOPIK REGRESI LINIER MENGGUNAKAN VARIABEL INTERVENING - Herlina Herlina; Thing Thing Diputra (Universitas Bunda Mulia, 2018)
Implementation of the sobel formula on the web is used to predict the indirect effect between independent and dependent variables. This web application, can be used to perform simple regression analysis as well as multiple linear regression. A simple linear regression consists of one independent variable (x) and one dependent variable (y) that serves to find out how closely the relationship of two variables and know the contribution of the independent variable (x) in explaining the dependent variable and can make predictions. Double linear regression consists of two or more independent vaiabel (x) and one dependent variable (y). The data in this study can be either cross section or team series data. The purpose of implementation of sobel formula is to facilitate the researchers by utilizing the internet network that is connected on the web. The result of the implementation of the sobel formula is on the site https://thingdiputra.github.io/Keywords: Linear regression, intervening variable, sobel formula